Evaluation of Marine Tourism Management Policy in Takabonerate National Park, Selayar Regency - Nasir (International Journal of Tourism Management and Hospitality, 2025)
Takabonerate National Park is one of the marine conservation areas that has great potential in the development of marine tourism in South Sulawesi. However, the increase in tourism activities in this region presents challenges in maintaining environmental sustainability and local community involvement. This study aims to evaluate the effectiveness of marine tourism management policies in Takabonerate National Park, especially in terms of policy implementation, community participation, and its impact on the environment and socio-economy. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that although management policies have been prepared normatively through zoning and visit regulations, in practice there are still obstacles such as limited human resources, weak supervision, lack of community involvement in decision-making, and uneven distribution of economic benefits. In addition, uncontrolled tourism activities have the potential to damage the marine ecosystem which is the main attraction of this region. Based on these findings, it is suggested the need to strengthen institutional capacity, increase coordination between agencies, active community involvement, and develop more inclusive and sustainable management policies. With this approach, it is hoped that marine tourism management in Takabonerate National Park can provide economic benefits while maintaining optimal environmental sustainability.